Social Network Forensics, Cyber Security, and Machine Learning - Krishna, P. Venkata; Gurumoorthy, Sasikumar; Obaidat, Mohammad S. (SpringerBriefs in Forensic and Medical Bioinformatics, 2019)
This book discusses the issues and challenges in Online Social Networks (OSNs). It highlights various aspects of OSNs consisting of novel social network strategies and the development of services using different computing models. Moreover, the book investigates how OSNs are impacted by cutting-edge innovations.